Management of severe capecitabine-induced corneal toxicity - Mathieu Heyvaert; Hannelore Denys; Jo Van Dorpe; Dimitri Roels (American Journal of Ophthalmology Case Reports, 2024)
Purpose: To describe the clinical presentation and management of severe capecitabine-induced corneal toxicity. Observations: A 71-year-old woman presented with severe bilateral vision loss. Four months earlier, capecitabine was initiated for a metastatic invasive ductal carcinoma. Biomicroscopy revealed bilateral whorl-like corneal epitheliopathy accompanied by metaplasia, keratinization and subepithelial fibrosis. After consulting the treating oncologist, capecitabine treatment was discontinued. Initially, a non-surgical approach was adopted and intensive topical dexamethasone treatment was applied. Despite capecitabine discontinuation and topical steroid treatment, visual acuity progressively declined. Bilateral corneal scraping and bandage contact lens fitting was performed. This resulted in significant improvement of visual acuity, corneal surface regularity and quality of life. Conclusion and importance: We report the first case of severe visual impairment due to capecitabine-induced corneal toxicity. Early corneal scraping, especially when confronted with profound vision loss, may yield better outcomes compared to relying on spontaneous recovery after capecitabine discontinuation. Patients experiencing ocular discomfort and vision loss, while receiving capecitabine therapy, should be referred for semi-urgent ophthalmological examination.